Our experience of treating diaphyseal fractures of the forearm bones in children - Shermatov, Gayrat; Khodzhaev, Rakhmonberdy (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2010)
Diaphyseal fractures of the forearm bones in children are the most frequent injuries of the locomotor system and make 45.0–68.2 % of all fractures of bones in children. Treatment of patients with such fractures is one of urgent and difficult problems in modern traumatology. The conservative method of treatment is applied in 70–80 % of cases. It is indicated for fractures without any displacement of bone fragments or with a displacement which has been successfully eliminated in a closed way, as well as in the presence of contraindications to a surgical intervention. This method consists in closed reduction of the fragments followed by their subsequent fixing with a plaster bandage. A circular splint bandage is placed from the distal palmar crease to the middle or upper third of the humerus in the supine position. Oblique, comminuted and isolated diaphyseal fractures of the forearm bones are the most difficult ones for treatment. According to literature data, the structure of techniques for surgical treatment of the above fractures does not contain any minimally invasive methods, which would make it possible to constantly receive favourable functional results. Despite constant improvement of methods for treating the above injuries, this problem is still far from being solved.